PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. BANK SULSELBAR CABANG BANTAENG - Almunawwar, Fahruni; Arniati, Arniati; Rasyid, Muh Nur (Jurnal Ekonomi Sakti, 2025)
This study aims to examine the influence of work discipline and work environment on employee productivity at PT. Bank Sulselbar Bantaeng Branch. The research uses a quantitative approach with a saturated sampling technique involving the entire population of 37 employees. Data collection was carried out through the distribution of questionnaires using a Likert scale as a measurement tool. The data obtained were analyzed using multiple linear regression analysis with the assistance of SPSS version 26. The results indicate that work discipline and work environment have a positive and significant effect on employee productivity. This is evidenced by the t-values for work discipline (2.234) and work environment (3.109), both of which are greater than the t-table value of 2.035, with significance levels below 0.05. Based on these findings, it can be concluded that strong work discipline and a conducive work environment can optimally enhance employee productivity. Keywords: Work Discipline, Work Environment, Employee Productivity.